Bite Marks as a Form of Physical Abuse in Intimate Partner Violence Against Men - A Millaty Dirgahayu; Djumadi Ahmad; Denny Mathius; Zulfiyah Surdam (Fakultas Kedokteran Universitas Muslim Indonesia, 2026)
Background: Intimate partner violence (IPV) is a pervasive public health and human rights issue that can affect individuals of all genders. While women are disproportionately affected, male victims are often underreported and underserved. Bite marks, though sometimes underestimated, represent a violent and intimate form of physical abuse. Content: A 26-year-old male presented with multiple bite marks on the upper arm, shoulder, and chest, consistent with patterned injuries typical of human dentition. The injuries were inflicted by his female partner during a domestic altercation. In addition to the bite wounds, the victim sustained a puncture wound to the chest caused by a ballpoint pen. This event marked an escalation in the pattern of abuse that the victim reported had been ongoing for over a year. This case highlights the complexity of IPV, especially when the victim is male. Bite marks are often inflicted during close physical struggle and are typically associated with intense emotional states, such as rage or control. From a forensic perspective, bite marks can serve as critical evidence linking the perpetrator to the act of violence. The use of an improvised weapon (a pen) in this case also underscores the impulsivity and escalation potential of IPV. Summary: This case underlines the need for a gender-inclusive approach to IPV evaluation and management. Medical and forensic professionals should be trained to recognize bite injuries and respond appropriately to male victims, ensuring comprehensive documentation, evidence collection, and referral for psychosocial support.